Teleworking during the COVID-19 pandemic: Determining factors of perceived work productivity, job performance, and satisfaction - Loredana Mihalca; Tudor Irimiaș; Gabriela Brendea (Amfiteatru Economic Journal, 2021)
Due to the COVID-19 pandemic, telework has been adopted extensively as a way to ensure business continuity. However, its effects on important employee outcomes such as work productivity, job performance, and satisfaction are unclear. The purpose of this study was to investigate whether the factors previously identified as important determinants of telework effectiveness are also relevant in the context of the pandemic. Drawing on Baruch and Nicholson's Model of Teleworking, the relationship between individual, home/family, job, and organizational factors and adjustment to telework during COVID-19 was examined. Survey data was collected from 482 employees who worked from home on a full-time basis during the pandemic. Results indicated that individual factors (i.e., self-management tactics) and home/family factors (i.e., the need for adequate telework conditions) are important predictors for employee productivity, performance and satisfaction while teleworking during COVID-19. Furthermore, workload (i.e., job factor) was a significant predictor for work productivity and satisfaction with telework. Surprisingly, organizational support for teleworking was not related to any of these outcomes. Implications for research and practice concerning telework during the pandemic are discussed.
Keywords: J22; D23; 330; teleworking; COVID-19; productivity; workload; self-management; job satisfaction; teleworkers